2015
DOI: 10.2147/ndt.s77909
|View full text |Cite
|
Sign up to set email alerts
|

Linking emotional distress to unhealthy sleep duration: analysis of the 2009 National Health Interview Survey

Abstract: ObjectiveThe objective of the study was to examine the independent association of emotional distress with unhealthy sleep duration (defined as <7 or >8 hours).MethodsData from the 2009 National Health Interview Survey (NHIS), a cross-sectional household survey, were analyzed to investigate the associations of emotional distress with unhealthy sleep durations, adjusting for sociodemographic factors, health risks, and chronic diseases through hierarchical multiple logistic regression analysis.ParticipantsA total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 30 publications
6
35
1
Order By: Relevance
“…Sleep and wakefulness are disrupted by a variety of factors, including those that are physiologic, behavioral, and environmental (24). It also is well documented that psychological distress disturbs sleep (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep and wakefulness are disrupted by a variety of factors, including those that are physiologic, behavioral, and environmental (24). It also is well documented that psychological distress disturbs sleep (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…48 Insomnia is aggravated by long distance travel and jet lag, which can trigger psychotic relapse. This association was first reported in 1959, 49 with many more reports appearing since.…”
Section: Post Travel Jet Lagmentioning
confidence: 99%
“…Although distress is a construct that embraces three domains-psychological, behavioral and somatic symptoms [1]-it is usually assessed with standardized scales such as Hospital Anxiety and Depression Scale (HADS) [3] or Beck Depression Inventory (BDI) [4], which are self-report questionnaires focused on the associated aspects of anxiety and depression symptoms [1,5,6]. In addition to these, there are tools that measure non-specific distress [7][8][9] such as the Kessler Psychological Distress Scale [10,11] which is widely used to screen for mental disorders in the middle-aged general population. Finally, there is also the Psychological Distress Manifestations Measure Scale (PDMMS) designed to explore comorbidity among symptoms [12], but it is not a diagnostic tool as it was developed in a nonclinical population [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated the bidirectional relationship between distress and unhealthy sleep defined as sleep with a duration less than 7 hours or longer than 8 hours [7,9,13,14]. Evidence indicates that emotional distress is associated with changes in sleep architecture, total sleep time, sleep quality, sleep efficiency, rapid eye movement sleep, sleep onset latency, and slow wave sleep [9,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation